2018
DOI: 10.1073/pnas.1706754115
|View full text |Cite
|
Sign up to set email alerts
|

Roll maneuvers are essential for active reorientation of Caenorhabditis elegans in 3D media

Abstract: Locomotion of the nematode is a key observable used in investigations ranging from behavior to neuroscience to aging. However, while the natural environment of this model organism is 3D, quantitative investigations of its locomotion have been mostly limited to 2D motion. Here, we present a quantitative analysis of how the nematode reorients itself in 3D media. We identify a unique behavioral state of-a roll maneuver-which is an essential component of 3D locomotion in burrowing and swimming. The rolls, associat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…Animals exposed to noxious chemicals applied to their tails accelerate forward ( Hilliard et al 2002 ). In the wild, additional strategies, including three dimensional maneuvers, are likely to be employed ( Bilbao et al 2018 ).…”
Section: Behavioral Strategies Used To Track Toward or Avoid Chemicalmentioning
confidence: 99%
“…Animals exposed to noxious chemicals applied to their tails accelerate forward ( Hilliard et al 2002 ). In the wild, additional strategies, including three dimensional maneuvers, are likely to be employed ( Bilbao et al 2018 ).…”
Section: Behavioral Strategies Used To Track Toward or Avoid Chemicalmentioning
confidence: 99%
“…It remains to be shown whether these features hold when worms are presented with more complex multisensory inputs, or engaged in behaviours other than the aforementioned action cycle such as mating [ 38 ] or nictation [ 39 ]. Moreover, it is still unclear to what extent the manifold can encode or control the postural diversity in worm behaviour that has been reported [ 40 ], or three-dimensional locomotion [ 41 ]. So far, studies have shown that the manifold is preserved under different developmental [ 37 ] and feeding [ 29 ] conditions.…”
Section: An Updated View Of Sensorimotor Control In C Elegmentioning
confidence: 99%
“…Complementing the NemaFlex assay, we also tested mutants in the burrowing environment where the muscles of C. elegans might be challenged differently due to the three-dimensional movement (55,56). In the burrowing assay, mutants are loaded at the bottom of well-plate and then stimulated to burrow through the Pluronic gel towards an attractant on the top (Figure 3A).…”
Section: Genetic Defects In Sarcomeres Can Reduce C Elegans Muscle Stmentioning
confidence: 99%